Search For Love In Kamala Das’ Poetry: Exploring the Themes of Love and Companionship in Kamala Das' Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
If we throw a closer look at Kamala Das’s poems, one can find easilythat love, sex, marriage and companionship were major concerns to her. Questfor love has been the prominent feature and preoccupation of Kamala Das. Sheanalyzes love’s several facets and basically her love poetry can be groupedinto two parts. In the first part, the physical love is quite important and insecond part Das’ concern can be seen towards real love. To her ideal love meansthe sort of relation that exists between the lord Krishna and Radha? It is thevery phase of love, where lovers leave their egos or narrow outlook to minglewith each other. On the other hand, the first phase signifies the lovers whoare not ready to sack their egos which come in their way to have perfect love.